High-transmittance and focal controllable plano-convex lenses with embedded nanolens bottoms formed by electrowetting on a colloidal monolayer. Issue 8 (2nd January 2020) - Li, Xiangmeng; Shao, Jinyou; Tian, Hongmiao; Li, Xiangming; Chen, Xiaoliang; Zhu, Xijing
Abstract : UV-curable polymer lenses with a nanolens array decorated on the bottom surface via irreversible electrowetting on a hydrophobic colloidal monolayer. Abstract : Combination of high transmittance and controllable focal length for plano-convex lenses is critical for various optical systems but has been a challenge. Here we demonstrate a strategy to overcome this challenge by introducing the electrowetting of a UV-curable polymeric material on a colloidal monolayer into the formation of plano-convex lenses.